THE ROLE OF TUTORS IN SELF-DIRECTING THE LEARNING OF THE STUDENTS OF NURSING - Amador Fierros, Genoveva; Chávez Acevedo, Ana María; Alcaraz Moreno, Noemí; Moy López, Norma Angélica; Guzmán Muñiz, Jorge; Tene Pérez, Carlos Enrique (Investigación y Educación en Enfermería, 2008)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Problem-Based Learning method is based on constructivist theories of learning, the principles of adult learning and the development of andragogical models. Its objective is to help students develop skills to direct their own learning. Objective: to analyse the role of professors of the bachelor’s degree in nursing as facilitators of self-directed learning Licenciatura in nursing of the University of Colima Mexico. Methodology: with the use of a descriptive survey integrated with 20 items answered by 121 students, we assessed the role of the professors of a bachelor’s degree in nursing. The 20 items assessed three areas of the facilitation process: Management of information, group process and reflection and critical thinking. These items were verified with Cronbach’s alpha and a reliability of 0.96. Results: when the KruskalWallis survey was conducted, statistically signi.cant differences were found only with regard to the “Group processing” dimension among sophomores and juniors (H = 6.77; P < 0.05). Even though no statistically signi.cant differences were found with regard to the other dimensions, it is possible to detect shifts in the students’ opinion trend about the role of tutors. Conclusion: The overall average score per scale makes it possible to conclude that the “the work of the tutor” is viewed favourably, considering that the students report that their tutor “almost always” facilitates, assists, promotes or collaborates on the development of the skills for being a self directed learner.